Prognostic role of pretreatment plasma fibrinogen in patients with solid tumors: A systematic review and meta-analysis. Issue 10 (December 2015) - Perisanidis, C.; Psyrri, A.; Cohen, E.E.; Engelmann, J.; Heinze, G.; Perisanidis, B.; Stift, A.; Filipits, M.; Kornek, G.; Nkenke, E.
Highlights: The prognostic value of baseline plasma fibrinogen in solid tumors was assessed. High fibrinogen is associated with poor prognosis of patients with cancer. High fibrinogen relates to worse survival in non-metastatic and metastatic cancer. Plasma fibrinogen might be integrated in cancer staging systems. Plasma fibrinogen could improve treatment decision-making in patients with cancer. Abstract: Background: Plasma fibrinogen may be involved in several stages of cancer progression. Clinical studies have demonstrated that pretreatment plasma fibrinogen is associated with poor survival in various cancers. The aim of this meta-analysis was to examine the prognostic effect of circulating fibrinogen in solid tumors. Materials and methods: We searched Medline, EMBASE, Cochrane Database of Systematic Reviews, and meeting proceedings to identify studies assessing the effect of pretreatment plasma fibrinogen on survival of cancer patients. Pooled multivariable-adjusted hazard ratios (HRs) for overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS) were estimated using random-effects models. Results: Data from 52 observational studies and 15, 371 patients were summarized. An elevated baseline plasma fibrinogen was significantly associated with worse OS (pooled HR = 1.69; 95% CI = 1.48–1.92). The highest negative effect of elevated plasma fibrinogen on OS was demonstrated in renal cell carcinoma (pooled HR = 2.22), followed by head and neck cancer (pooled HR = 2.02), and colorectal cancer (pooled HR = 1.89). The adverse prognostic impact of high plasma fibrinogen remained in both non-metastatic and metastatic disease and patients of different ethnicity. Patients with high baseline fibrinogen had a significantly shorter DFS (pooled HR = 1.52) and CSS (pooled HR = 2.50). Conclusions: An elevated pretreatment plasma fibrinogen significantly correlates with decreased survival in patients with solid tumors. Future clinical trials are warranted to determine whether plasma fibrinogen could be incorporated in cancer staging systems and whether fibrinogen-lowering therapies have a favorable effect on disease recurrence and mortality.